Vitamin D Metabolism and Effects on Pluripotency Genes and Cell Differentiation in Testicular Germ Cell Tumors In Vitro and In Vivo - Blomberg Jensen, Martin (Neoplasia Press Inc., 2012)
Testicular germ cell tumors (TGCTs) are classified as either seminomas or nonseminomas. Both tumors originate from carcinoma in situ (CIS) cells, which are derived from transformed fetal gonocytes. CIS, seminoma, and the undifferentiated embryonal carcinoma (EC) retain an embryonic phenotype and express pluripotency factors (NANOG/OCT4). Vitamin D (VD) is metabolized in the testes, and here, we examined VD metabolism in TGCT differentiation and pluripotency regulation. We established that the VD receptor (VDR) and VD-metabolizing enzymes are expressed in human fetal germ cells, CIS, and invasive TGCTs. VD metabolism diminished markedly during the malignant transformation from CIS to EC but was reestablished in differentiated components of nonseminomas, distinguished by coexpression of mesodermal markers and loss of OCT4. Subsequent in vitro studies confirmed that 1,25(OH)(2)D(3) (active VD) downregulated NANOG and OCT4 through genomic VDR activation in EC-derived NTera2 cells and, to a lesser extent, in seminoma-derived TCam-2 cells, and up-regulated brachyury, SNAI1, osteocalcin, osteopontin, and fibroblast growth factor 23. To test for a possible therapeutic effect in vivo, NTera2 cells were xenografted into nude mice and treated with 1,25(OH)(2)D(3), which induced down-regulation of pluripotency factors but caused no significant reduction of tumor growth. During NTera2 tumor formation, down-regulation of VDR was observed, resulting in limited responsiveness to cholecalciferol and 1,25(OH)(2)D(3) treatment in vivo. These novel findings show that VD metabolism is involved in the mesodermal transition during differentiation of cancer cells with embryonic stem cell characteristics, which points to a function for VD during early embryonic development and possibly in the pathogenesis of TGCTs.